Improving Motivation to Perform in Learning: A Study of The Influence of Two-Dimensional Media, Interest in Learning and The Value of Hard Work Character - Lase, Famahato Lase; Noibe Halawa (EDUPEDIA Publisher, 2024)
Achievement motivation can be formed, developed and improved through learning. The aim of this research is to reveal the influence and contribution of the independent variable to the dependent variable using associative quantitative methods. The research population was all students of the Indonesian language and literature education study program FKIP Nias University and the sample was drawn by purposive sampling as many as 44 people in semester IV. The data collection instrument was a closed questionnaire and analyzed using inferential statistics using multiple linear regression techniques. The research results reveal that: (1) there is a partially significant influence of two-dimensional learning media (X1) on increasing achievement motivation in learning (Y) and every increase in X1 of 1.00% will be followed by an increase in Y of 0.728%; (2) there is a partially significant influence on interest in learning (X2) on increasing Y and every increase in X2 of 1.00% will be followed by an increase in Y of 0.329; (3) there is a partially significant influence of the hard work character value (X3) on the increase in Y and every increase in X3 of 1.00% will be followed by an increase in Y of 0.627; and (4) there is a significant influence together of the variables X1, X2, and X3 on Y and every increase in X1, X2, and X3 of 1.00% will be followed by an increase in Y of 1,684%. It is recommended for lecturers to use this two-dimensional learning media in organizing learning, arousing and developing interest in learning, and increasing the value of students' hard work character in order to achieve achievement motivation in learning.